Equipment life prediction based on genetic algorithm under Weibull distribution - Othman, Khalid Talib; Hamid, Qusay Essam (International Journal of Psychosocial Rehabilitation, 2020)
This paper studies the problem of equipment reliability life prediction under the Weibull distribution. The improved genetic algorithm is mainly used to improve the genetic algorithm coding, objective function and genetic operation to realize the estimation of Weibull parameters. The Weibull distribution model is obtained and the reliability life model of the equipment.